Ti-derived intermediate band in MgH₂ - Sheripov, U.; Zhanabergenov, Zh.; Uteniyazov, A.; Ismailov, K.; Karazhanov, S. (Functional Materials, 2012)
This article deals with a study of electronic structure of Ti-doped MgH₂ by the first-principles calculations. We show that Ti impurity substituting Mg (TiMmg) forms an intermediate band in the band gap of MgH₂, which is partially filled with electrons. However, the intermediate bands are well localized around Ti impurity. So, the effective masses of electrons in this intermediate band can be said to be infinite, it means that the electrons in these bands are immobile, and MgH₂:Ti remains to be an insulator. The energy estimated from the topmost valence band (conduction band) to Fermi level is ≥ 2.8 eV. Since the band gap of MgH₂ is ~ 5.6 eV, the energy between the conduction band minimum and Fermi level is also 2.8 eV. So despite presence of the intermediate band MgH₂ remains to be transparent to the visible part of the solar spectra and slightly reflective to the infrared light with very low light absorption.